Genetics and current treatment strategy of colorectal cancer - Islam, Muhammad (International Journal of Medicine, 2017)
This review aims to sketch a current scenario of colorectal cancer (CRC). Findings say that males are the most susceptible to CRC than the females. BRAF and RAS mutations are known as common causes of CRC. Not only targeted therapy but also a combination of radio- and chemotherapy is very useful in CRC.